Pendugaan Erosi Tanah dan Arahan Rehabilitasi Lahan berbasis SIG di DAS Wai Ela Negeri Lima Jazirah Leihitu Pulau Ambon - Sisilia Wariunsora; Rafael M Osok; Silwanus Talakua (Universitas Pattimura, 2020)
The occurrence of soil erosion in Wai Ela Watershed is related to natural factors such as geology, soil types, slope steepness, and land uses. This study aimed to estimate soil erosion rates and their spatial distribution in Wai Ela watershed, and the results were used to establish land rehabilitation practices. The study used a survey method with a flexible grid observation distance, and field data collection was conducted on 15 sampling areas representing 72 land units. The annual soil erosion rates of Wai Ela watershed were estimated by using RUSLE and GIS, and the results were corrected with 0,2547 (Talakua and Osok’s correction factor). The proposed land rehabilitation practices were established based on the tolerable soil erosion (T) values and CP maximum. The study results showed that the average annual erosion rates in Wai Ela watershed vary from light erosion (8,14 t/ha/yr) to very heavy erosion (381,70 t/ha/yr), while the tolerable soil erosion rates range from 4,60 t/ha/yr to 24t/ha/yr. The proposed land rehabilitation practices include enrichment of the existing unprotected areas (bare lands) with forest and fruit trees, planting cover crops and grasses, and mulching on agricultural land. Keywords: correction factor 0,2547, land rehabilitation practices, RUSLE, Wai Ela watershed ABSTRAK Erosi pada DAS Wai Ela terjadi akibat faktor alam yaitu geologi, jenis tanah, panjang dan kemiringan lereng dan penggunaan lahan. Tujuan penelitian adalah menduga besarnya erosi di DAS Wai Ela, dan menetapkan arahan rehabilitasi lahannya. Metode yang digunakan adalah survei dengan tipe observasi fleksible grid dan pengumpulan data lapangan dilakukan pada 15 sampel area yang mewakili 72 satuan lahan. Besarnya erosi dihitung menggunakan metode RUSLE dan hasilnya dikoreksi dengan factor 0,2547, dan dipetakan menggunakan program SIG. Hasil penelitian menunjukkan bahwa rrosbi di DAS Wai Ela berkisar dari sangat ringan (8,14 ton/ha/thn) hingga erosi sangat berat (381,70 ton/ha/thn), sedangkan erosi yang dapat dibiarkan atau nilai T berkisar dari 4,6 ton/ha/thn hingga 24 ton/ha/thn. Arahan rehabilitasi lahan yang disarankan adalah melakukan pengkayaan pada lahan-lahan yang terbuka dengan tanaman hutan dan buah-buahan, menanam tanaman penutup tanah dan rumput pada lahan yang miring dan penggunaan mulsa serasah/jerami, pada lahan-lahan pertanian. Kata kunci: DAS Wai Ela, faktor koreksi 0,2547, usulan rehabilitasi lahan, RUSLE